Structural and Gelation Characteristics of Alkali-Soluble β-Glucan from Poria cocos - Zhixing Li; Chenglei Sun; Fan Wang; Zhaofei Xia (Gels)
Alkali-soluble polysaccharides from Poria cocos (APCP) are typically discarded due to poor water solubility and limited bioavailability, despite their β-(1→3)-glucan backbone suggesting potential for functional applications. This study aimed to explore the structural characteristics, gelation behavior, and the capacity of APCP to reduce silver ions. Structural analysis confirmed that APCP is a homogenous β-(1→3)-D-glucan with a molecular weight of 314.2 kDa and a PDI of 1.32. A pH-mediated strategy enabled the formation of stable single-component APCP hydrogel (APCPH) with tunable mechanical strength, high swelling capacity (>590%), and thermal stability. The APCPH further acted as both a reducing and stabilizing matrix for in situ AgNP formation. Notably, the Ag-APCP hydrogel exhibited distinct antibacterial activity, with inhibition zones reaching 5.31 mm against Staphylococcus pseudintermedius. These findings demonstrate the feasibility of transforming underutilized APCP into multifunctional hydrogel platforms for green nanomaterial synthesis and biomedical applications. Future studies will focus on optimizing AgNP synthesis parameters and evaluating long-term stability and biocompatibility for translational use in antimicrobial therapies.